SO2 Poisoning Behaviors of Ca-Mn/TiO2 Catalysts for Selective Catalytic Reduction of NO with NH3 at Low Temperature. (31st March 2014) - Tian, Qingqing; Liu, Hongfeng; Yao, Weiyuan; Wang, Yan; Liu, Yue; Wu, Zhongbiao; Wang, Haiqiang; Weng, Xiaole
Abstract : The sulfur tolerance of Ca modified MnO x /TiO2 catalysts in low-temperature SCR process was investigated. Experimental results revealed that the durability of developed catalysts in the presence of SO2 could be improved by Ca modification. After being subjected to a range of analytical techniques, it was found that the surface Ca species could act as a SO2 trap by preferentially reacting with SO2 to form bulk-like CaSO4, inhibiting the sulfation of active phase. Furthermore, the introduction of SO2 had also preserved part of Lewis sites over the MnO x . Both of these are conducive to NH3 adsorption and activation at low temperature, hence improving the sulfur tolerance of Ca doped catalysts.